[OP.7D.07] INFLUENCE OF RENAL SYMPATHETIC DENERVATION ON BLOOD PRESSURE VARIABILITY: EXPERIENCE AT 11 EUROPEAN EXPERT CENTERS. (September 2016) - Persu, A.; Gordin, D.; Jacobs, L.; Thijs, L.; Bots, M.L.; Miroslawska, A.; Spaak, J.; Rosa, J.; De Jong, M.; Berra, E.; Elmula, F.E. Fadl; Wuerzner, G.; et al.
Abstract : Objective: Sympathetic tone is one of the main determinants of blood pressure (BP) variability. The aim of our study was to assess the changes in BP variability after renal sympathetic denervation (RDN) in resistant hypertensive patients, and, conversely, to look for the predictive value of baseline BP variability on mean BP changes after RDN. Design and method: Twenty-four hour BP measurements were analyzed in 167 resistant hypertensive patients recruited at 11 expert centers within the European Network Coordinating research on Renal Denervation (ENCOReD) (mean age 56.7 years; 40 % women; mean baseline office BP: 172/98 mmHg; 24-h ambulatory BP: 152/90 mmHg), both at baseline and after RDN. Blood pressure variability was assessed by the weighted standard deviation (SDw), average real variability (ARV), coefficient of variation (CV) and variability independent of the mean (VIM) of 24-h ambulatory BP. Results: After an average follow up of 6.7 months, mean office and 24-h ambulatory BP fell by 15.4/6.6 mmHg and 5.5/3.7 mmHg respectively (P < 0.0001 for both). Whereas no significant changes in ARV or CV were observed, SDw and VIM for 24-h systolic BP decreased by −1.29 mmHg (95%CI: −2.17 to −0.42; P < 0.01) and −1.11 mmHg (95%CI: −1.92 to −0.30; P < 0.01), respectively. Decrease in these systolic BP variability estimates remained significant in multivariable-adjusted analyses and was paralleled by similar changes for 24-h diastolic BP. Finally, baseline SDw (P = 0.0006), ARV (P = 0.012) and VIM (P = 0.04) were significantly correlated with mean changes in diastolic - but not systolic - BP after RDN. Conclusions: Renal denervation was associated with a significant decrease in BP variability independent of the mean, which in the long term may decrease cardiovascular risk. Furthermore, baseline BP variability was predictive of diastolic BP changes after RDN. These results are consistent with the known influence of sympathetic nervous system on BP variability and peripheral vascular resistances. Our findings need confirmation in randomized controlled studies testing second-generation RDN catheters, preferably including younger patients with higher sympathetic tone and less advanced vascular damage.